Analysis of Structural Violence in Stephen King’s Carrie (1974): A Galtungian Perspective - Al haq, Dzohiroh Fathiah; Istiani, Imas (Universitas Pahlawan Tuanku Tambusai, 2025)
This article examines the significance of violence, particularly structural violence—as a critical topic of literary research. Violence is a persistent and evolving element of human life, making it essential to explore its forms and implications. As societies have developed through the establishment of governments, regulations, and institutions, structural violence has become increasingly prevalent. This form of violence manifests as indirect harm embedded within social, economic, and political systems, often disadvantaging specific individuals or groups through financial hardship, unequal access to education, healthcare disparities, and discrimination. Notably, structural violence often goes unnoticed and lacks a clearly identifiable perpetrator. The purpose of this study is to analyze the portrayal of violence, with a focus on structural violence, in Stephen King’s novel Carrie. Employing a qualitative method, this research draws upon textual evidence from the novel to support its analysis. The findings reveal that Carrie reflects various instances of structural violence through its narrative, particularly those that inflict invisible wounds on the victim. However, this study is limited to institutionally embedded forms of violence, leaving broader dimensions of the topic open for future exploration.